MEMS optical switch based on fiber displacement - Leow, C. W.; Mohammad, A. B. (2006)
A MEMS optical switch based on fiber displacement is presented. The switch consists of an arrangement of electrostatic actuated cantilever beams. A movable fiber is attached to the cantilevers as such that it gets displaced as the cantilevers are actuated. By aligning another fiber towards the end of this movable fiber, a simple on/off switch is achieved. The switch can be extended to 1x2 by aligning 2 fibers at the receiving end. Design and modeling of the switch is done using a mixture of finite element and boundary element method, utilizing Coventor, a commercial MEMS modeling software. The switch can be utilized in optical monitoring and test equipment subassembly system.